The effects on stability region of the fractional-order PI controller for one-area time-delayed load-frequency control systems - Celik, Vedat; Ozdemir, Mahmut Temel; Bayrak, Gokay (Sage Publications Ltd, 2017)
One of the controllers used in load-frequency control systems is the PI controller, taking account of time delay originating from measurement and communication. In control systems, along with the use of the fractional-order controller, computing parameter space exhibited stable behaviour on the controller parameters and analysing its efficiency have become a significant issue. This study focuses on computing the effects of the fractional integral order () on the stable parameter space for the control of a one-area delayed load-frequency control system in the case of a fractional-order PI controller. The effect of time delay on the stable parameter space is also investigated at different fractional integral orders () in the time-delayed system with fractional-order PI controller. For this purpose, a characteristic equation of the delayed system with the fractional-order PI controller is obtained, and the stable parameter spaces of the controller are computed according to the fractional integral order () and time delay () values using the stability boundary locus method, which is graphics based. Moreover, the generalized modified Mikhailov criterion is used for testing the stability region on the K-p-K-i plane. The obtained results verified that the stability region on the K-p-K-i plane change depending on the and .
Keywords: Fractional-order PI controller; generalized modified Mikhailov criterion; load-frequency control system; stability boundary locus; stability region; time-delay systems